Engineering composites properties and applications - Salit, Mohd Sapuan (Universiti Putra Malaysia Press, 2014)
In the recent years, there is a growing interest in the application of composite materials in industrial and engineering sectors particular being driven by many potentials that they offer such as light weight, high specific strength and stiffness, part integration, corrosion resistance and low manufacturing cost compared to their metal counterparts. Nowadays the use of composites is not only restricted to polymer based composites but has expanded to metal and ceramic matrix composites and the most recent one is nanocomposites. This book is focusing on the properties, characterization, design, fabrication and application of engineering composites. The major aim of publishing this book is to gather the research finding and information performed by researchers involved in engineering composites research ranging from natural fibre composites, glass filled composites, laminated composites, metal matrix composites, reinforced concrete composites, and nanocomposites in the wide of applications such as automotive, aerospace, manufacturing, chemical, packaging, construction, agriculture and marine engineering. This book is equally beneficial for the readers from research and academic communities and for general readership.